Rapid and Simultaneous Detection of Major Drug Resistance Mutations in Reverse Transcriptase Gene for HIV-1 CRF01_AE, CRF07_BC and Subtype B in China Using Sequenom MassARRAY® System - Cheung, Ka-Wai (PLoS One, 2016)
The development of a rapid, high-throughput and cost-effective HIV-1 drug resistance (HIV-DR) testing system is a challenge for areas consisting different HIV-1 strains. In this study, we established a broadly reactive multiplex assay that could simultaneously detect major drug resistance mutations at 8 loci, which are associated with resistance to commonly used nucleoside reverse transcriptase inhibitors (NRTIs) and Non-nucleoside reverse transcriptase inhibitors (NNRTIs), in specimens of HIV-1 CRF01_AE, CRF07_BC and subtype B, the three major circulating strains in China, using the matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) provided by Sequenom MassARRAY® system. To establish the assay, pol gene fragments were prepared from the plasma viral RNA of 159 patients by nested PCR and the presence of wild type and mutant alleles at the 8 loci were analyzed by MALDI-TOF MS. In terms of loci, the detection rate of the alleles was greater than 97% for M41L, K65R, M184V and G190A, 91.2% for K101E/Q/P, 91.2% for T215F/Y, 89.9% for K103N/S and 80.5% for L210W. In terms of individuals, 80% of the alleles were detected in 95.4% CRF01_AE patients, 100% CRF07_BC patients and 83.3% subtype B patients. Importantly, the MALDI-TOF MS results were concordant to the drug resistance profiles of patients obtained from conventional sequencing analysis after excluded the failed detections. Using plasmid templates, the assay was estimated to be sensitive to detect drug resistant variants at level about 20% of the circulating viral population. The capability of this assay to detect mixed viral populations was further verified by two different patient specimens. In conclusion, this study evaluated the use of Sequenom MassARRAY® system for high-throughput detection of HIV-DR mutations towards the commonly used reverse transcriptase inhibitors in China.